Efektifitas Penggunaan Analisis Stochastic Oscillator Dan Moving Average Convergence-Divergence Pada Perdagangan Saham-Saham Perbankan di Bursa Efek Indonesia - Siahaan, Debora; Muda, Iskandar; Irawati, Nisrul (Owner : Riset dan Jurnal Akuntansi, 2024)
The objective of the research is to find out how effective stochastic oscillator and moving average convergence-divergence (MACD) technical analysis is in yielding capital gain and abnormal return, viewed from descriptive analysis, analysis of effects, and disparity test analysis by using some theories and previous research results. This research uses daily stock closing price data from the issuers in banking su-sector of the research period of 2015-2019. The research employs descriptive analytic approach, regression analysis and disparity test, supported by IBM SPSS version 25 software. The result of the descriptive analysis shows that buy and sell stochastic oscillator and MACD signals are effective in yielding capital gain. The result of regression analysis shows that gain signal yielded by indicator of Stochastic Oscillator and MACD has significant effects on capital gain in which the probability value (Asymp. Sig) of Stochastic Oscillator on capital gain is 0.000, and the probability value (Asymp.Sig) of MACD on capital gain is 0.000. The result of the disparity test analysis shows that there is no difference in abnormal return in the pre and post appearance of gain signal in Stochastic Oscillator and in MACD